Work-from-Home and Wage Convergence Across Cities: An Exploration - Jan K. Brueckner; David R. Agrawal (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
This paper provides evidence on a WFH-related hypothesis that has not previously been tested empirically. The hypothesis is that the presence of fully remote workers, for whom residence and work locations are decoupled, should create a tendency toward wage convergence across cities within teleworkable occupations. The reason is that, since fully remote workers can work anywhere, local wages must match those available in other cities for employers to attract any of these workers. By combining occupational wage data with data on which occupations are teleworkable, the paper attempts to test the wage-convergence hypothesis. The results are mixed, but some evidence does emerge in favor of the hypothesis.
Keywords: R23; J60; 330; work-from-home; telework; wages; convergence